2000
DOI: 10.2527/2000.7882039x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics and relative bioavailability of supplemental organic zinc sources for poultry and ruminants.

Abstract: Eight commercially available organic Zn products and reagent-grade ZnSO4 x 7H2O (Zn Sulf) were evaluated by polarographic analysis, and solubility in .1 M K2HPO4-KH2PO4 buffer (pH 5), .2 M HCl-KCl buffer (pH 2), and deionized water. Fractions from these solubility tests were evaluated by gel filtration chromatography for structural integrity. Degree of chelation was generally positively related to chelation effectiveness determined by polarography. The organic sources were Zn methionine complex A (Zn MetA), Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
112
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(133 citation statements)
references
References 25 publications
9
112
2
4
Order By: Relevance
“…The percentage of Zn present in a soluble form (Zn solubility) may be related to digesta pH (Figure 1) (7% to 16%, respectively) and 10% to 18% of Zn were soluble in piglet stomach and intestine, while these percentages were 26% to 32% and 9% to 14% in the broiler gizzard and intestine, respectively. Furthermore, Zn solubility was also found to be higher as a consequence of lower pH in vitro (Cao et al, 2000). The stomacal Zn solubility was low (54% to 84% on 100 kg BW pigs) compared to measures observed by Dintzis et al (1995) even though pH was 4.5 and extraction methods for measuring soluble Zn were similar.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The percentage of Zn present in a soluble form (Zn solubility) may be related to digesta pH (Figure 1) (7% to 16%, respectively) and 10% to 18% of Zn were soluble in piglet stomach and intestine, while these percentages were 26% to 32% and 9% to 14% in the broiler gizzard and intestine, respectively. Furthermore, Zn solubility was also found to be higher as a consequence of lower pH in vitro (Cao et al, 2000). The stomacal Zn solubility was low (54% to 84% on 100 kg BW pigs) compared to measures observed by Dintzis et al (1995) even though pH was 4.5 and extraction methods for measuring soluble Zn were similar.…”
Section: Discussionmentioning
confidence: 74%
“…Previous Schlegel, Nys and Jondreville research suggested that Zn availability depends on Zn solubility in the digesta (Susaki et al, 1999), whereas Zn solubility may depend on various factors including digesta pH (Cao et al, 2000;Jongbloed et al, 2002), dietary Zn concentration (Dintzis et al, 1995;Susaki et al, 1999), supplemented Zn source (Cao et al, 2000) and interactions between dietary Zn and diet composition (Ammerman et al, 1995;Jongbloed et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The data from Analysis I suggests that broilers are more efficient in using ZN N than piglets and the data from Analysis II show that ZN N was negatively affected by PP NH in piglets and that Phytase S was more efficient in piglets to improve ZN N bioavailability than in broilers. Zinc bioavailability results from dietary Zn solubility in the digestive tract before absorption (Susaki et al, 1999), which is dependent from pH conditions (Cao et al, 2000;Jongbloed et al, 2002). Early in 1963, Lease measured that 66% of Zn from soybean meal was soluble when the raw material was previously digested with pepsin at pH 3, followed with an alcalinization to pH 6.8.…”
Section: Description Of the Databasesmentioning
confidence: 99%
“…Close and Cole, 2003), it is possible to say generally, that the complex zincmethionine, is about two times more available than zinc oxide. CAO et al (2000) reported that the absorption of zinc-proteinate, zinc-amino acid chelate and zinc-polysaccharide were 83 to 139 percent of zinc sulfate (set at 100 %). Further, ŠIMEK et al (2000) observed that addition of zincmethionine had positive impact on increasing production and milk quality, fertility and health.…”
mentioning
confidence: 99%